Forsa pilot evaluation baseline survey results - Gilligan, Daniel O.; Kurdi, Sikandra; Tabe-Ojong, Martin Paul Jr.; Yassa, Basma (International Food Policy Research Institute, 2022)
The Forsa program, launched in 2021 by the Egyptian Ministry of Social Solidarity has been designed as a graduation program targeted to current beneficiaries of the Takaful cash transfer program. To understand how well Forsa supports household income generation and to better understand the beneficiary household characteristics which may relate to program success, the International Food Policy Research Institute in collaboration with the Ministry of Social Solidarity is running a randomized control trial of the pilot Forsa program (see IFPRI MENA Regional Program Policy Note 21 for more details on the program and evaluation design). A baseline household survey collected in January-February 2022 provides a detailed picture of the eligible households in the targeted communities, including the employment situation and work-related skills of the household members intending to participate in Forsa. The household survey data was collected in the eight governorates of the pilot: Beni-Suef, Sharqia, Qalyoubia, Luxor, Fayoum, Menia, Souhag, and Assuit. 24 households Forsa-eligible households were surveyed in each of 323 communities: 16 households from the pool of current Takaful beneficiaries and 8 from the pool of Takaful rejected applicants. The final sample size was 7,752 households. Each household was asked whether they were willing to enroll in Forsa and, if so, which household member would participate in the trainings. 83% of sampled eligible households indicated willingness to enroll in Forsa. The large majority of these (77%) indicated a preference for the self-employment track.